2020
DOI: 10.3390/en13174382
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Spillover and Hedging among Carbon, Biofuel and Oil

Abstract: In recent years, there has been growing interest in the market interactions between carbon (or clean/renewable energy) and traditional fossil energy such as coal and oil, but few studies have discussed their dynamic volatility spillover and time-varying correlation. To investigate these issues, we used the weekly data of the European Union carbon emission allowance (EUA) futures, biofuel and Brent oil prices from 25 October 2009 to 5 July 2020. We employed the vector autoregressive-generalized autoregressive c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Further research focused on volatility spillover impacts and dynamic correlation utilising diverse multivariate GARCH models. Boersen and Scholtens (2014), Koch (2014), Chang et al (2019), and Lee and Yoon (2020) have demonstrated the existence of a positive correlation and significant comovements between emissions and oil prices. However, Chang et al (2019), has pointed out the presence of weaker correlation and spillover between emissions and oil prices compared with coal and natural gas using an asymmetric BEKK model.…”
Section: Crude Oil Price and Carbon Dioxide Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research focused on volatility spillover impacts and dynamic correlation utilising diverse multivariate GARCH models. Boersen and Scholtens (2014), Koch (2014), Chang et al (2019), and Lee and Yoon (2020) have demonstrated the existence of a positive correlation and significant comovements between emissions and oil prices. However, Chang et al (2019), has pointed out the presence of weaker correlation and spillover between emissions and oil prices compared with coal and natural gas using an asymmetric BEKK model.…”
Section: Crude Oil Price and Carbon Dioxide Emissionsmentioning
confidence: 99%
“…Fisher-Vanden et al, 2004;Oh et al, 2010;Andersson and Karpestam, 2013;Alshehry and Belloumi, 2015;Li et al, 2018;Mensah et al, 2019;Wang et al, 2019;Agbanike et al, 2019;Malik et al, 2020;Ullah et al, 2020) and on the other hand, studies have investigated the relationship of oil prices with CO 2 emission allowances prices (e.g. Koljonen and Savolainen, 2005;Diebold and Yilmaz, 2009;Liu and Chen, 2013;Koch, 2014;Hammoudeh et al, 2014;Boersen and Scholtens, 2014;Hammoudeh et al, 2015;Tan and Wang, 2017;Zeng et al, 2017;Wang and Guo, 2018;Ji et al, 2018;Chevallier et al, 2019;Chang et al, 2020;Lee and Yoon, 2020;Wang and Zhao, 2021;Zheng et al, 2021).…”
Section: Crude Oil Price and Carbon Dioxide Emissionsmentioning
confidence: 99%
“…The results are consistent with Chevallier (2012), who found a dynamic correlation of [−0.05; 0.05] between oil and the CO 2 futures' prices of the European Climate Exchange (ECX) using data from 2005 to 2008. Additionally, several studies have confirmed the existence of a positive correlation and considerable co-movements between CO 2 emissions and oil prices (Boersen and Scholtens, 2014;Koch, 2014;Chang et al, 2019;Chen et al, 2019;Lee and Yoon, 2020).…”
Section: Dynamic Conditional Correlations Among the Variablesmentioning
confidence: 90%
“…The opposite is also true. The issue of risk and oil prices was also discussed by Lee and Yoon [41]. They found the effect of volatility spillover from the Brent oil market to the European Union carbon emission allowance (EUA) market.…”
Section: Introductionmentioning
confidence: 98%